Molecular mechanism in trigeminal nerve and treatment methods related to orthodontic pain. (9th November 2021) - Tang, Ziwei; Zhou, Jiawei; Long, Hu; Gao, Yanzi; Wang, Qingxuan; Li, Xiaolong; Wang, Yan; Lai, Wenli; Jian, Fan
Abstract: Background: Orthodontic treatment is the main treatment approach for malocclusion. Orthodontic pain is an inevitable undesirable adverse reaction during orthodontic treatment. It is reported orthodontic pain has become one of the most common reason that patients withdraw from orthodontic treatment. Therefore, understanding the underlying mechanism and finding treatment of orthodontic pain are in urgent need. Aims: This article aims to sort out the mechanisms and treatments of orthodontic pain, hoping to provide some ideas for future orthodontic pain relief. Materials: Tooth movement will cause local inflammation. Certain inflammatory factors and cytokines stimulating the trigeminal nerve and further generating pain perception, as well as drugs and molecular targeted therapy blocking nerve conduction pathways, will be reviewed in this article. Method: We review and summaries current studies related to molecular mechanisms and treatment approaches in orthodontic pain control. Results: Orthodontics pain related influencing factors and molecular mechanisms has been introduced. Commonly used clinical methods in orthodontic pain control has been evaluated. Discussion: With the clarification of more molecular mechanisms, the direction of orthodontic pain treatment will shift to targeted drugs.